Synthesis of 5- and 6-donor schiff base ligands for the selective extraction and transport of selected base metals ions - Ogutu, Hezron Felix Odhiambo (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.